The Analysis of S.T.E.M Education Lesson Plan in Curriculum 2013 - Rahmaniar, A.; Purnamasari, S.; Abdurrahman, D.; Setyawarno, D.; Mahmoud, H. A. (Universitas Negeri Yogyakarta, 2024)
The integration of STEM (Science, Technology, Engineering, and Mathematics) Education is essential to develop students' abilities, such as creativity, critical thinking, collaboration, and communication. Teachers should create a lesson plan that integrates STEM education to implement STEM Education into the learning process. The purpose of this research is to analyze the lesson plans from preservice teachers in science education programs and establish a standardized lesson plan that integrates STEM Education. The method used descriptive analysis that describes the characteristics of STEM Education lesson plans using a rubric, adapted from another journal. The rubric has 20 indicators to analyze the lesson plans, with four levels - no evidence of, inadequate, needs improvement, and adequate. Most of the lesson plans met the standard but still require improvement and development. For the identity section, 50% of the lesson plans needed improvement. For the learning process, more than 50% of the lesson plans required improvement, but they were adequate for scientific activities. For the assessment and resources section, there was an equal distribution of lesson plans that needed improvement and adequate level. However, up to 70% of the lesson plans were on an adequate level for using a different media in the learning process.